Governance of Public Sector Organizations
XIII, 343 p.
Keywords: Governance of Public Sector Organizations a nalyzes recent changes in government administration by focusing on organizational forms and their effects. Contributors to this edited volume demonstrate how generations of reform result in increased complexity of government organizations, and explain this layering process with multiple theories.